Identificação de dengue em pacientes com síndrome febril aguda - Souza, Natália Vasconcelos de (2016)
Dengue is considered one arbovirus more important transmitted to humans. Of the Agreement with the World Health Organization (WHO) estimated that between 50-100 million people infected annually arise in over 100 Countries. Medium 550 thousand patients require hospitalization and 20,000 die from the disease. However, most cases are asymptomatic and can generate a not in seeking medical care and, as a consequence, an underestimation of the disease cases. The present study aimed to identify the main symptoms presented those participants with clinical suspicion of dengue, attended in primary care and tertiary institutions located in Fortaleza. Were evaluated 114 participants with clinical suspicion of dengue were recruited in and Clinic in the ward of São José Hospital for Infectious Diseases and NAS Units Primary Health Care (UAP) Mattos Dourado and Francisco Pereira de Almeida, in Fortaleza, in the period January 2013 to December 2014. The specific diagnosis of testicular done paragraph dengue Were: NS1 immunoassay, enzyme-linked immunosorbent ELISA IgG and IgM. Of the 114 participants, 78 (68.42%) Were Positive paragraph dengue in less than hum hair testicles Specific done, BEING 74 (64.9%) IgM Positive paragraph, 3 (2.6%) for NS1 and 1 (0, 8%) participants was positive in both techniques. The most affected age group was between 20-39 years old, being diagnosed with dengue participants in all month recruitment. There was considerable a incidence patients with possible secondary infection, suggesting a wide circulation make any Ceara State viruses, making it necessary an application effective actions paragraph once the transmitter agent and containment a greater awareness of the population. As samples used for IgM ELISA Test realization collected were do 1 at the 5th day of symptoms, not being the suggested by WHO to Test procedure, however getting a high positivity, these results show the need for more studies a fence application of this tool paragraph to get more early human diagnosis, allowing que this patient be conducted faster way, assisting in your so improvement and preventing que of this evolve for tables more graves.